Antibodies directed against annexin A2 and obstetric morbidity. (November 2016) - Salle, V.; Schmidt, J.; Smail, A.; Mazière, C.; Conte, M.A.; Brulé, A.; Mazière, J.C.; Cadet, E.; Herpe, Y.E.; Duhaut, P.
Highlights: Annexin A2 can be recognized by antibodies in sera from patients with obstetric complications in early or later stages of pregnancy. The prevalence of anti-annexin A2 antibodies was higher compared as that of anti-annexin A5 antibodies. Anti-annexin A2 antibodies were detected independently of antiphospholipid and anti-annexin A5 antibodies. Further studies are needed to determine whether annexin A2 is critical for maintenance of placental integrity. Abstract: Acquired and inherited thrombophilia have both been reported to be associated with an increased risk of obstetric complications in early or later stages of pregnancy. Annexin A2 (ANXA2) is strongly expressed in vascular and placental tissues and plays a crucial role in fibrinolysis. The aim of the present study was to evaluate the prevalence of antibodies directed against ANXA2 in patients with recurrent miscarriage or obstetric complications. Anti-ANXA2 antibodies (aANXA2) were detected by ELISA in the sera from 46 women with obstetric morbidity, mainly recurrent miscarriage. The cut-off value for positivity was defined as 3 standard deviations above the mean optical density (OD) obtained in the sera from 42 female blood donors. The prevalence of aANXA2 in patients and healthy individuals was 15.2% and 2.3%, respectively. A statistically significant difference was observed between the 2 groups in terms of aANXA2 IgG titers (p = 0.01). The highest aANXA2 levels were observed in sera from 2 patients with recurrent miscarriage and one patient with preeclampsia. aANXA2 could play a role in thrombotic mechanisms leading to recurrent pregnancy loss and placental vascular disease. Further studies are needed to determine whether ANXA2 is critical for maintenance of placental integrity.